Designing Controller for Joined Dynamic Nonlinear PEMFC and Buck Converter System - M.R. Rahimi Khoygani; R. Ghasemi; D. Sanaei (Institute of Advanced Engineering and Science, 2014)
Designing controller for a class of dynamical nonlinear model for Polymer Electrolyte Membrane Fuel Cell (PEMFC) is discussed in this paper inwhich the PEMFC system is used for powering a Notebook PC (Processing Computer). The power requirement of a Notebook PC varies significantly under different operational conditions. The proposed feedback controller is applied for the buck dc/dc converter to stabilize the load voltage at a desirable level under various operational conditions. The simulation results show the promising performance of the proposed controller at the different operating conditions.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5195